(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
The efficiency of iron electrode based electrocoagulation (EC) technique at laboratory scale to remove lead (Pb) from battery industrial effluent in Bangladesh is investigated. Different combinations of voltage (15, 30 and 45), effluent pH (1, 3, 5, 7 and 9) and electrolysis time (15, 30, 45 and 60 minutes) at the EC reactor was examined for searching the ideal operating conditions of maximum lead removal. Initial battery effluent pH of 3, electro coagulating at 30 V for 15 minutes would be the optimum conditions for treatment where 99.9% Pb removal was achieved. Treated effluent quality was compared with national environmental standard to discharge into surface water bodies and found physico-chemical parameters (TDS, TSS, DO and pH) were within prescribed limit except electrical conductivity. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 125-134, 2015